Synthesis of Gold Nanoparticles Using Tannin-Rich Extract and Coating onto Cotton Textiles for Catalytic Degradation of Congo Red - Penwisa Pisitsak; Kwandee Chamchoy; Varanrada Chinprateep; Wiphawan Khobthong; Pisutsaran Chitichotpanya; Sarute Ummartyotin (Journal of Nanotechnology)
Gold nanoparticles (AuNPs) were synthesized under ambient conditions from chloroauric acid in aqueous solution at pH 4. Tannin-rich extract from Xylocarpus granatum bark was used as both reducing and capping agent, rapidly converting Au (I) salt to AuNPs. Transmission electron microscopy showed the as-prepared AuNPs to be predominantly spherical, with an average diameter of 17 nm. The AuNPs were tested for catalytic reduction of Congo red (CR), a carcinogenic azo dye, in aqueous sodium borohydride solution. Cotton samples were coated with the AuNPs, taking on a reddish-purple color. The samples showed significantly reduced tearing strength after coating, though tensile strength was unaffected. UV-visible spectroscopy was used to determine the dye concentration in the water. CR degradation was observed only when AuNPs were present, and the efficiency of degradation was strongly linked to the AuNP loading. The AuNP-coated fabrics left only a 4.7% CR concentration in the solution after 24 h and therefore promise as a heterogeneous catalyst for degradation of CR in aqueous solution.